New expression vector for microalgae - Ariff, Arbakariya; Kadkhodaei, Saeid; Abd Rahim, Raha; Ling, Tau Chuan; Memari, Hamid Rajabi; Abbasilli, Sahar; Akhavan, Morvarid; Tan, Joo Shun; Ramanan, Ramakrishnan Nagasandra (2014)
The present invention relates to expression vectors for the improved production of recombinant proteins in microalgae through synthetic biology. The present invention also relates to the construction of a vector system which can be used for promoter analysis in gene expression.